An investigation of the crude oil in the Spivey-Grabs field of south-central Kansas: an insight into oil type and origin - Kwasny, Brianna (Kansas State University, 2015)
The most common practice of typing crude oils utilizes biomarkers to gain insight on the history of the oil. This practice only considers the organic chemistry of the oil, and does not consider the trace element concentrations within the oil. Rare earth element and other trace element concentrations in crude oil might provide further insight into the oil’s source and origin. This study analyzed REE and other trace metal concentrations of crude oil in the Spivey-Grabs field of south-central Kansas through analysis by ICP-MS and ICP-AES that, coupled with visual physical characteristics of oil and FT-IR analysis, could explain the reported “compartmentalization” of the field and provide insight on the origin of the oils. Analysis of physical characteristics of the crude oils suggested the presence of two types of oil, of differing viscosities, in the field. FT-IR confirmed the presence of these two oil types based on functional groups present in the oils. The existence of a high viscosity oil could potentially explain the compartmentalization behavior in the field. PAAS-normalized REE distribution patterns showed a general LREE enrichment, a positive cerium and negative europium anomaly, and a MREE and HREE depletion, but higher viscosity oils showed additional MREE and HREE enrichment. K/Rb values ranged from 2,864 to 44,118, with oils from mixed-viscosity wells having lower ratios overall. K/Rb values of Spivey-Grabs crude oils more closely resembled those of the Lansing-Kansas City formation than the K/Rb values of the Woodford shale and Mississippian formation of the Anadarko basin. Comparing the rare earth element distribution patterns and K/Rb values from this study to those of the Woodford shale suggests the Spivey-Grabs oil originated from a local source and not from the Woodford shale.
Keywords: Geology; Spivey-Grabs Field; Rare earth elements; Trace metals; Geochemistry of crude oil; Mississippi Chert; Geochemistry (0996); Geology (0372)